'The dreadful catastrophe that happened at Asterton': a hurricane or an avalanche in Shropshire?. (2nd January 2022) - Bowen, James P.
ABSTRACT: This paper reconstructs the course of an event that happened at Asterton in south Shropshire in the late eighteenth century which at the time was attributed to a hurricane. Having reviewed the surviving evidence, in particular a contemporary account written by Reverend Edward Rogers as well as the coroner's inquisition report, newspaper articles, historic meteorological data, and the physical landscape, it will be argued that it was in all probability an avalanche rather than a hurricane. The causes and effects of avalanches which regularly occur in mountainous areas like the French and Swiss Alps are well understood, having long attracted the attention of physical geographers. However, in the eighteenth and early nineteenth centuries relatively little was known about these natural phenomena. Travellers often noted observing avalanches and contemporaries published accounts of them such as that which occurred at Bergemoletto in the Italian Alps in 1755. The interpretation of the event at Asterton as a hurricane illustrates how the understanding of avalanches as well as other natural phenomena was developing in the eighteenth century.